Association of retinopathy with risk of all-cause and specific-cause mortality in the National Health and Nutrition Examination Survey, 2005 to 2008 - Gui, Si-Yu; Wang, Xin-Chen; Qiao, Jian-Chao; Lin, Si-Yu; Wang, Qian-Qian; Zhang, Meng-Yue; Xu, Yue-Yang; Huang, Zhi-Hao; Tao, Li-Ming; Hu, Cheng-Yang; Tao, Fang-Biao; Jiang, Zheng-Xuan; et al. (Frontiers in Public Health, 2023)
This is a provisional file, not the final typeset article Methods: In this prospective cohort study, a total of 6797 participants aged over 40 years based on NHANES 2005NHANES -2008 were analyzed. The severity of retinopathy was classified into 4 grades-no retinopathy, mild non-proliferative retinopathy (NPR), moderate to severe NPR, and proliferative retinopathy (PR). Multiple covariate-adjusted Cox proportional hazards regression models and Fine and Gray competing risk regression models were used to assess the all-cause and cause-specific mortality risks, respectively. The propensity score matching (PSM) approach was also applied additionally to adequately balance between-group covariates to validate our findings.Results: A final total of 4808 participants representing 18,282,772 United States (US) nonhospitalized participants were included for analysis, 50.27 % were male (n = 2417), 55.32 % were non-hispanic white (n = 2660), and mean [SE] age, 56.10 [0.40] years. After a median follow-up of 12.24 years (interquartile range, 11.16-13.49 years), 1,164 participants died of all-cause mortality, of which 941 (80.84%) died without retinopathy and 223 (19.16%) died with retinopathy at baseline. The presence of retinopathy was associated with increased all-cause mortality, cardiovascular disease (CVD), and diabetes mellitus (DM)-specific mortality, and the results remain consistent after PSM.Severity analysis showed that only mild NPR was associated with an increased all-cause mortality risk (hazard ratio (HR)=2.01; 95% confidence interval (CI), 1.00-4.03), while increased CVD and DM-specific mortality risk were associated with all grades of retinopathy and were exponentially greater with increasing retinopathy severity, and the trend test was also significant (P for trend 0.004 and 0.04, respectively). Discussion: Our findings suggest that the diagnosis of retinopathy is an independent risk factor for all-cause mortality in people over 40 years old. Retinopathy grading is significantly associated with the survival risk of patients with CVD or DM, it can be a valuable predictor in the stratified management and risk warning of CVD or DM patients, as well as in the monitoring of systemic vasculopathy status.